The Effect Of The Use Of The Toothbrush Calendar On The Brushing Behavior On Students Of SDIT Insan Mulia Merangin Jambi - Astuti, Syurmi; Nurdin, Nugi; Novviadi, Pitri; Oktriyedi, Ferly (Poltekkes Kemenkes Kendari, 2023)
Dental and oral health is still a problem in society that needs to be considered. Based on The Global Burden of Diseases Study 2016, dental and oral health problems are diseases experienced by almost half of the world's population of 3.58 billion people. This study aimed to determine the effect of using a toothbrush calendar on the behavior of brushing teeth and mouth of students of SDIT Insan Mulia Merangin Jambi. This type of research is analytical in nature with a quasi-experimental design (Quasi Experiment) as a result of certain treatments, one group pretest, and posttest designs, this design does not have a comparison or control group. The approach taken was done three times, namely before the experiment, after the 7th day of the experiment, and after the 14th day of the experiment. This research was conducted at SD IT Insan Mulia Jl. Patimura RT.38 RW.01 km.03, Pematang Kandis Village, Kec. Bangko, Kab. Merangin Prov. Jambi. The time of research was carried out in June 2022 for 16 days. The results of research on the effect of toothbrush calendar on tooth brushing behavior in SD IT Insan Mulia Merangin Jambi students can be concluded that: (1) Toothbrush calendar significantly affects knowledge; (2) Toothbrush calendar significantly influences attitude; (3) Toothbrush calendar significantly influences action; (4) Toothbrush calendar significantly affects plaque.